Pengaruh Program Insentif Financial Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai variable Intervening (Studi Pada PT Wangsa Jatra Lestari) - Andriansyah, Muhammad Rafi'; Achmad, Nur (ITB AAS Indonesia Surakarta, 2025)
This research focuses on the effect of financial incentive programs and career development on employee performance, with job satisfaction as a mediating variable, at PT Wangsa Jatra Lestari. The research methods used is quantitative with the PLS-SEM approach. A total of amounted to 98 respondents of PT Wangsa Jatra Lestari employees who were selected using purposive sampling technique. The findings reveal that financial incentives and career advancement positively and significantly influence employee performance. In addition, financial incentive programs and career progression show a positive and meaningful impact on employee job satisfaction. Than, job satisfaction is proven to serve as a mediating variable between financial incentives and career development toward employee performance outcomes. These results suggest that job satisfaction plays a vital part in strengthening the effect of financial incentives and career development on performances. This study implies that organizations should consistently enhance transparent and transparent incentive programs, as well as develop clear and systematic career paths to improve employee satisfaction and performance.